Mobile cities, modelling policies: Importing/exporting the Singapore ‘model’ of development - WOODS, Orlando (Institutional Knowledge at Singapore Management University, 2017)
A recent focus of research has been the making, mobility and mutations of urban policy. The global circulation of urban models – or exemplars of best practices and values that are deemed to be desirable and achievable – has gained significant traction. Such models are those that are dislocated from their place of origin, and transplanted to an adopted site. This chapter draws on the case of Singapore: one of the most emblematic examples of an importable/exportable urban model – a prototype for growth-oriented urban development with its normative and technical plans for growth and management – to foreground problems and challenges associated with such importation/exportation. We propose a future research agenda that focuses on the sites of origination and application of urban models, and the ways in which social, political, cultural, economic and environmental contexts shape policy transfer – not to mention urban theory – around the world